Birds of different feathers: coaches' perspectives of cultural diversity and team dynamics in professional sport - Eluère, M.; Martin, L. J.; Godfrey, M.; Mallett, C. J.; Heuzé, J.-P. (International Sport Coaching Journal, 2024)
As the number of international transfers increases in professional sport teams, it is unclear how this diversity impacts team functioning, and also, whether coaches feel equipped to meet this new challenge. In this study, we explored professional coaches` perceptions and experiences of cultural diversity (i.e., national and racioethnic diversity), with a specific emphasis on implications for team dynamics. Semistructured interviews were conducted with nine professional coaches from four interdependent team sports in France (i.e., basketball, football, handball, volleyball). The coaches had experience leading first or second division men`s and/or women`s teams (e.g., two highest national championships in France, Canada, or Italy) and national teams (e.g., France, Belgium, China). Based on a critical realist approach, results indicated that coaches purposefully considered cultural diversity within their teams, and discussed stereotypical differences based on nationalities pertaining to work ethic, communication, and motives for action. Coaches` international experience and intercultural competence seemed to be key elements that influenced their willingness to consider the cultural diversity of their teams in their coaching/management strategies. Herein, we discuss the importance of purposefully considering a team`s context (e.g., sport, member composition, geographical location) and note that coach intercultural competence appears to be a concept warranting further investigation